1988
DOI: 10.1073/pnas.85.2.406
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a mitogen-activated S6 kinase.

Abstract: Treatment of Swiss mouse 3T3 cells with epidermal growth factor, orthovanadate, or serum results in the activation of a kinase that phosphorylates protein S6 of the 40S ribosomal subunit in vitro. This kinase is eluted as a single peak of activity from either a Mono Q anion-exchange column at 0.34 M NaCl or a Mono S cation-exchange column at 0.20 M NaCl. Treatment of the peak fraction from the Mono S column with phosphatase 2A completely abolishes the activity of the enzyme. The kinase appears to be distinct f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
0
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(117 citation statements)
references
References 46 publications
3
113
0
1
Order By: Relevance
“…Polyomavirus middle T antigens lacking tyrosine 315, a major site of phosphorylation by pp6Ocsr" in immune complexes, have impaired transforming potential (12,42 (2,24,32,37).…”
Section: Discussionmentioning
confidence: 99%
“…Polyomavirus middle T antigens lacking tyrosine 315, a major site of phosphorylation by pp6Ocsr" in immune complexes, have impaired transforming potential (12,42 (2,24,32,37).…”
Section: Discussionmentioning
confidence: 99%
“…When activated by the convergence of mTOR-and PI3K-dependent signals, S6K1 functions as an in vivo kinase toward the 40S ribosomal protein S6 (Jeno et al, 1988), which has been suggested to increase the translational efficiency of a class of mRNA transcripts that contain a terminal oligopyrimidine (TOP) tract at their 5 0 -end (Jefferies et al, 1994(Jefferies et al, , 1997Terada et al, 1994). Many of these 5 0 -TOP mRNAs encode components of the translation machinery, such as ribosomal proteins and elongation factors (reviewed in Sonenberg and Gingras, 1998).…”
Section: Signaling To S6k1: Regulation Of Ribosome Biogenesis?mentioning
confidence: 99%
“…One PI 3-kinase-dependent pathway required for mitogenic signaling involves p70 s6k (15,16). This enzyme was initially identified as a kinase capable of phosphorylating the ribosomal S6 protein in a growth factor-sensitive manner (17,18). Phosphorylation of S6 is thought to regulate the synthesis of proteins whose transcripts contain 5Ј-oligopyrimidine tracts.…”
mentioning
confidence: 99%